Estimated Impact of Covid-19 on Exchange Rate Risk of Multinational Enterprises Operating in Emerging Markets - Arvi, Leonard; Manakyan, Herman; Khazeh, Kashi (International Journal of Economics and Financial Issues, 2023)
Multinational enterprises (MNE) operating in emerging countries are exposed to various types of risk. Exchange rate risk is an important and anticipated part of MNE’s total risk exposure, with a variety of tools available to mitigate that risk. In this study, we focus on transaction exposure of cash flows in eight distinctive emerging market currencies and employ the Modified Value-at-Risk (MVaR) model to estimate the maximum one-period loss during an eighteen-month period spanning pre- and post-Covid-19 periods. The predicted losses by MVaR are then compared to the ex-post results, to identify any differences in the pre- and post-Covid-19 periods and to determine the need for adjustments in hedging strategies by MNEs during similar global crises. The motive of this research is to understand the limitations of hedging and what MNEs can do to mitigate transaction exposure risk. The results provide insights on whether MNEs should hedge their currency risk or not. The COVID-19 pandemic did impact all firms globally, so this study is relevant and pertinent as firms plan their post-pandemic growth.